Penerapan Aplikasi Simkah Web Perspektif Teori Efektifitas Budiani - Abdul Rozak Mustofa; Gilang Difa Nur Rochim (Jurnal Penelitian Agama, 2023)
Marriage registration has the aim of providing legal certainty to the bride and groom. BIMAS Islam under the auspices of the Ministry of Religion has launched an application to be used as a means of recording marriages, namely SIMKAH Web. In its implementation there are obstacles that occur in each region, these obstacles are in the form of facilities and officers who are still having difficulty understanding the application as experienced by KUA Mantrijeron. This study was conducted to answer the question of what are the supporting and inhibiting factors for implementing marriage registration using SIMKAH Web at KUA Mantrijeron and also the effectiveness of SIMKAH Web in implementing marriage registration.The theory used in this research is Soerjono Soekanto's theory of effectiveness and law enforcement. This type of research is a field research (field research). The nature of this research is descriptive analytic and uses a normative approach. The data collection method used in this research is Observation, Interview and Documentation. There are differences with previous research, namely in the use of the theory of effectiveness and the use of the latest regulations. The results of the study, namely the use of SIMKAH Web in marriage registration at KUA Mantrijeron there are still several obstacles. One of the problems is that the community is not well socialized, so people do not take advantage of the self-registration menu that has been provided. In addition, the SIMKAH Web application which returns manual input makes KUA operators return to work as before the SIMKAH Web, meaning that it is not automatic. Then when viewed from the indicators specified in the theory of effectiveness, the application of SIMKAH Web on marriage registration at KUA Mantrijeron is not effective because it does not meet the specified requirements.